Changes in locomotive rates during senior elite rugby league matches - Sykes, D.; Twist, C.; Nicholas, C.; Lamb, K. (Journal of Sports Sciences, 2011)
The aim of this study was to quantify the changes in locomotive rates across the duration of senior elite rugby league matches. A semi-automated image recognition system (ProZone 3, ProZone®, Leeds, England) was used to track the movements of 59 players from six teams during three competitive matches. The players were classified into one of four positional groups: props (n = 9), back row (n = 9), pivots (n = 14) or outside backs (n = 27). Players' movements were classified as low, high or very high intensity running and reported as locomotive rates (distance covered per minute played) for successive quarters of each match. Analysis of variance revealed that only the outside backs showed a significantly lower overall locomotive rate during the final quarter compared to the first (P < 0.05). However, locomotive rates for high and very high intensity running during the final quarter were significantly lower (P < 0.05) than the first quarter among outside backs, pivots and props despite no change in the rate of involvements in contact. On the basis of these findings, it is suggested that high and very high intensity running locomotive rates may be more affective methods of detecting fatigue during competitive matches than overall locomotive rate.